(untitled) (Research, Society and Development, 2019)
Dengue is a growing public health problem and has been neglected lately despite being the most prevalent arboviral disease in the world. This study aims to describe the epidemiological aspects of dengue in the state of Paraíba, Northeast Brazil, from 2007 to 2012. The data were extracted from clinical reports of the National System of Notification Disorders (SINAN) of Brazil provided by the computer department. SUS DATASUS of the Ministry of Health. We performed a descriptive analysis of the number of reported cases of dengue, according to year, race, age and sex and the diseases of the cases. From 2007 to 2012, 45231 suspected cases of dengue were reported. The years with high epidemic rates were: 2011 2007 and 2012 in descending order. There was a progressive decline in the incidence of dengue from 2008 to 2010. This study showed a predominance of cases in females, browns, aged between 20 and 39 years. In 33 cases the death resulted from hemorrhagic phenomena and other complications, however, the other 8 cases of death were due to different causes. Dengue remains an important health problem, with severe cases and high lethality. Given this, it is necessary to emphasize that public health policies should adopt and maintain preventive actions through health education, basic sanitation, good housing conditions.